Participating in Sports After Mitral Valve Repair for Primary Mitral Regurgitation: A Retrospective Cohort Study. Issue 5 (September 2021) - Blanc, Adrien; Lairez, Olivier; Cariou, Eve; Fournier, Pauline; Poenar, Ana Maria; Marcheix, Bertrand; Cron, Christophe; Grunenwald, Etienne; Porterie, Jean; Labaste, François; Elbaz, Meyer; Galinier, Michel; et al.
Abstract : Objective: Participating in either competitive or leisure sports is restrictive after surgical mitral valve repair (MVR). In this study, we examine the impact of sports on outcomes after MVR. Design: Retrospective cohort study. Setting: Patients aged 18 to 65 years who underwent a first-time MVR for primary mitral regurgitation (MR) in a tertiary care center. Patients: One hundred twenty-one consecutive patients were included in the study. The exclusion criteria were as follows: other concomitant procedures, early perioperative death or repeat intervention, noncardiac death or endocarditis during follow-up, and general contraindications for normal physical activity. Assessment of Risk Factors: Participation in sports was quantified by the number of hours per week during the past 6 months, classified according to the Mitchell classification and assessed with the International Physical Activity Questionnaire (IPAQ) short form. Main Outcome Measures: The primary composite endpoint was MVR failure defined as MR grade ≥2 or mean transmitral gradient ≥8 mm Hg, signs and symptoms of heart failure, or late-onset postoperative AF (>3 months). Results: The mean age was 50 ± 11 years, and there were 85 (71%) men. The median follow-up was 34 months [interquartile range (IQR): 20-50]. Fifty-six (46%) patients participated in sports regularly (median of 3 h/wk; IQR: 2-5). Twenty (17%) patients reached the primary composite endpoint with no correlation with participation in sports ( P = 0.537), IPAQ categories ( P = 0.849), in any of the Mitchell classification subgroups and a high level of participation in sports ≥6 hours ( P = 0.679). Conclusions: Sports seem to be unrelated to the worst outcome after MVR.